Analisa Kelayakan Usaha Tani Aren di Kecamatan Lareh Sago Halaban Kabupaten Lima Puluh Kota - Yulistriani Yulistriani; Edwin Edwin; Halimatus Syahdia Hasibuan; Muhammad Parikesit Wisnubroto; Dewi Rezki (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Indonesia has a potential for diversity in agricultural commodities and a tropical climate. Sugar palm is a commodity that has the potential to be developed. Opportunities for developing sugar palm agribusiness are still broad, from providing production inputs such as seeds, planting (the farm), harvesting, processing products, marketing, and supporting subsystems. Almost all palms are used and can be used for various needs. This research aims to analyze the feasibility of sugar palm farming in Lareh Sago Halaban District, Kab. Lima Puluh Kota. The quantitative research method calculates revenue, cost, and feasibility analysis of sugar palm farming. The research results show that the average fixed cost of sugar palm farming is IDR. 54.951.667 per hectare per year. The average variable cost of sugar palm farming is IDR. 20,233,333. The total average production cost of sugar palm farming is IDR. 75.185.000. The total revenue of sugar palm farming is IDR. 310,658,000 per hectare per year, consisting of fresh sap at IDR. 102,200,000 per hectare per year, palm sugar at IDR. 62,458,000 per hectare per year, and sugar palm at IDR. 146,000,000 per hectare per year. The R/C ratio for fresh sap is 1.35. For palm sugar, it is 0.83, and for ant sugar, it is 1.95. The feasibility analysis concluded that sugar palm farming is generally economically profitable, as evidenced by the feasibility values of fresh sap and palm sugar, which are greater than 1. Of the three products produced, palm sugar has the highest feasibility value (R/C = 1.95). In contrast, palm sugar has the lowest feasibility value or is not feasible with an R/C value of 0.83, which is less than 1.